2015
DOI: 10.1007/s00464-015-4267-x
|View full text |Cite
|
Sign up to set email alerts
|

Face validation of the Virtual Electrosurgery Skill Trainer (VEST©)

Abstract: Background Electrosurgery is a modality that is widely used in surgery, whose use has resulted in injuries, OR fires and even death. The SAGES has established the FUSE program to address the knowledge gap in the proper and safe usage of electrosurgical devices. Complementing it, we have developed the Virtual Electrosurgery Skill Trainer (VEST©), which is designed to train subjects in both cognitive and motor skills necessary to safely operate electrosurgical devices. The objective of this study is to asses the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A high-fidelity VR simulator would allow for skills training in both the advanced psychomotor and cognitive skills aspects of ESD. The simulator can be used to train not only endoscopists but also other operating room (OR) personnel (endoscopy nurses and technicians) in all of procedural aspects [23]. The advantages of endoscopy-based VR simulators can be summarized as: (1) no ethical dilemma with initial training through an apprentice model on human subjects, with no risk of harm to the patient or malpractice, since no-human subject is involved [24]; (2) repeatable on different tumor-types and sizes; (3) affordable compared to recurrent costs of other animate and inanimate training models [25,26]; (4) potentially reduced training time with a steeper learning curve once human ESD work commences [27]; (5) and quantifiable measurement for both assessment and training [28].…”
Section: Esd Training In the United Statesmentioning
confidence: 99%
“…A high-fidelity VR simulator would allow for skills training in both the advanced psychomotor and cognitive skills aspects of ESD. The simulator can be used to train not only endoscopists but also other operating room (OR) personnel (endoscopy nurses and technicians) in all of procedural aspects [23]. The advantages of endoscopy-based VR simulators can be summarized as: (1) no ethical dilemma with initial training through an apprentice model on human subjects, with no risk of harm to the patient or malpractice, since no-human subject is involved [24]; (2) repeatable on different tumor-types and sizes; (3) affordable compared to recurrent costs of other animate and inanimate training models [25,26]; (4) potentially reduced training time with a steeper learning curve once human ESD work commences [27]; (5) and quantifiable measurement for both assessment and training [28].…”
Section: Esd Training In the United Statesmentioning
confidence: 99%
“…Moreover, the treatment of such burns costs nearly US$600 million, which imposes a huge financial burden on hospitals (7). In 2009, the American Emergency Care Research Institute reported 550 to 650 cases of fire in operating rooms, 68% of which were caused by ESUs (8). In recent years, patient safety in the operating room is a cause for concern (9).…”
Section: Introductionmentioning
confidence: 99%
“…Its objective is to train surgeons in the motor and cognitive skills that are required to safely operate electrosurgery tools during open and minimally invasive procedures. A monopolar electrosurgery module was demonstrated at the 2014 SAGES learning center and users rated the module as realistic and useful to learning the fundamentals of electrosurgery [6]. A virtual OR fire training and prevention module was demonstrated at the 2015 SAGES learning center where the simulator was highly rated for its effectiveness and usefulness for OR fire safety and training [7].…”
Section: Introductionmentioning
confidence: 99%